Assessment of agro-morphological performance of twenty-four corn (Zea mays l.,) parent lines resistant to Striga hermonthica for determining hybrid parents - Annicet, N'da Huges; Dofougo, Konaté; Romaric1, Kouakou Kouakou; Laurent, N’cho Achi; Lassina, Fondio; Kouabenan, Abo (Future Science, 2025)
The data available on the study of corn parental lines against weeds in Côte d'Ivoire is still limited. The principal objective of the present study was to assess the agro-morphological performance of those resistant to Striga hermonthica. Specifically, the objective was to as-certain the hybrid parents of twenty-four individuals from IITA under conditions of artificial Striga infestation. The trials were conducted at the CNRA research station in Ferkessédougou, located in northern Côte d'Ivoire. The experimental design was a randomized complete block with three replications. Nine CIMMYT/IBPGR were used. Analy-sis of variance revealed significant differences between the lines about the different agro-morphological traits. Hierarchical ascending classification (HAC) revealed variability structured into four groups of morphological diversity. Group 2 and Group 4, respectively, con-tained the earliest (FM = 57.93 +- 1.72 and 58.62 ± 3.15) and most productive (NER = 21.25 +- 4.57 and 13.70 +- 2.77) lines, which also exhibit very good emergence density (DL = 28.25 ± 5.13 and 25.00 +- 7.50). Group 3 contained the intermediate lines (FM = 61.50 +- 1.88; FF = 63.18 +- 2.64; NER = 10.81 +- 5.27; DL = 23.12 +- 8.09). Group 1 contained the late lines (FM = 66.50 +- 2.82; FF = 68 ± 0.00), which demonstrated reduced productivity (NER = 3.75 +- 1.76) and exhibit-ed a low emergence density (DL = 9.25 +- 10.25). Discriminant factor analysis (DFA) identified nine parental lines in groups 2 and 4 that exhibited favorable characteristics about early maturity and produc-tivity. These lines may be used as hybrid parents in a program de-signed to enhance corn productivity in Côte d'Ivoire.